Purification of Recombinant Galectins Expressed in Bacteria - Prato, Cecilia Arahi (2020)
Galectins are soluble lectins that participate in many physiological and pathological functions. Since they can act extracellularly, the use of the recombinant protein is a recurrent strategy for studying their biological functions. Here, we provide a general protocol for the production of Galectins and their isolated or chimeric domains. We take advantage of their lectin activity and the 6xHis-tag addition for purification, thus obtaining a highly pure and active Galectin to use in both in vitro and in vivo assays. For complete details on the use and execution of this protocol, please refer to Cattaneo et al. (2011), Tribulatti et al. (2012), and Prato et al. (2020).